2016
DOI: 10.1027/1866-5888/a000146
|View full text |Cite
|
Sign up to set email alerts
|

Participative Supervisory Behavior and the Importance of Feeling Safe and Competent to Voice

Abstract: Abstract. In our field study of 147 employees and their supervisors, we tested a moderated mediation model, investigating how participative supervisory behavior relates differently to promotive and prohibitive voice. Overall, we found a significant effect of participative supervisory behavior on promotive and prohibitive voice, and this effect was mediated by psychological safety for prohibitive voice, but not promotive voice. Unexpectedly, we did not find a direct moderation effect of occupational self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Empirically, some research has suggested that leadership behaviors that encourage voice will facilitate subordinate voice via induced psychological safety, such as the leader's openness (Detert and Burris 2007) and the participative supervisory behavior (Svendsen, Jønsson and Unterrainer 2016). The findings of these studies imply that leadership behaviors that discourage voice may inhibit subordinate voice via reduced psychological safety.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, some research has suggested that leadership behaviors that encourage voice will facilitate subordinate voice via induced psychological safety, such as the leader's openness (Detert and Burris 2007) and the participative supervisory behavior (Svendsen, Jønsson and Unterrainer 2016). The findings of these studies imply that leadership behaviors that discourage voice may inhibit subordinate voice via reduced psychological safety.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Second, previous research on psychological safety has demonstrated that psychological safety is an important mediator that can pass the effect of leadership to subordinate voice (Edmondson and Lei 2014). However, most studies focused on positive leadership (Detert and Burris 2007;Svendsen, Jønsson and Unterrainer 2016;Walumbwa and Schaubroeck 2009), while few studies have focused on negative leadership. Our study contributes to the psychological safety literature by adding the evidence that negative leadership such as AL may also affect employee voice via the mediator of psychological safety.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Accordingly, both the antecedents and consequences of prohibitive voice are found to be different than for promotive voice. For example, studies by Liang et al (2012) and Svendsen, Jønsson and Unterrainer (2016) found that selfprotective motives such as psychological safety are more important for prohibitive voice than promotive voice. Moreover, studies have shown that speaking up with prohibitive concerns puts a larger strain on the employee, leads to lower performance ratings, and reduces promotion opportunities (Lin & Johnson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The past two decades have seen a large number of studies regarding the relationship between leadership and voice behaviour (cf. Detert & Burris, 2007;Duan, Li, Xu, & Wu, 2017;Dutton, Ashford, Lawrence, & Miner-Rubino, 2002;Liu, Zhu, & Yang, 2010;McClean, Burris, & Detert, 2013;Svendsen, Jønsson, & Unterrainer, 2016;Tangirala & Ramanujam, 2012). A leadership style that has been highlighted theoretically and empirically as an antecedent that may be especially effective in eliciting employees' ideas and concerns is ethical leadership -defined as the demonstration of normatively appropriate conduct through personal actions and interpersonal relationships and the promotion of such conduct to followers through two-way communication (Brown & Treviño, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The present research also extends the evolving body of work on employee voice by revealing a new antecedent of such behavior. While prior research has demonstrated that social relationships influence employees’ willingness to speak up (Morrison, ), the findings were limited to social interactions within organizations, including as pertaining to relationships with leaders (De Cremer & Wubben, ; Detert & Burris, ; Svendsen, Jønsson, & Unterrainer, ; Van Dyne, Kamdar, & Joireman, ), structural centrality within the organization (Venkataramani & Tangirala, ), and support from coworkers (Tucker, Chmiel, Turner, Herschcovis, & Stride, ). Our findings extend prior research by implying that employees' social relationship status (social rejection, in this case), regardless of organizational settings and interaction types, can predict their voice in the workplace.…”
Section: Discussionmentioning
confidence: 99%